SHARING SESSION INFORMASI BEASISWA INDONESIA BANGKIT SEBAGAI UPAYA PENINGKATAN KESEMPATAN MERAIH BEASISWA STUDI LANJUT - Arditya Prayogi; Nur Khotimah; Riki Nasrullah; Imam Prayogo Pujiono; Moh. Syaifuddin (Jurnal AbdiMas Nusa Mandiri, 2026)
Higher education plays a crucial role in human resource development, but limited funding and low scholarship literacy remain barriers for graduates seeking further study. This community service activity aims to improve scholarship literacy and participant readiness for the Indonesia Bangkit Scholarship selection process through an interactive online sharing session. The PkM activity employed a service learning approach and was held on May 20, 2025, featuring scholarship awardees to share strategies for registration, document preparation, and skills development. Forty-eight online participants attended the activity, and an impact evaluation was conducted using a post-activity satisfaction survey that assessed the usefulness, clarity of the material, and participants' readiness to prepare application documents. The evaluation results showed that participants found the activity beneficial and reported increased readiness in developing further study plans and preparing for selection. Overall, the sharing session, based on awardee experiences, has the potential to become an easily replicable empowerment model to expand access to scholarship information and strengthen readiness for further study.